Plasma membrane order and fluidity are diversely triggered by elicitors of plant defence - Sandor, Roman; Der, Christophe; Grosjean, Kevin; Anca, Iulia; Noirot, Elodie; Leborgne-Castel, Nathalie; Lochman, Jan; Simon-Plas, Françoise; Gerbeau-Pissot, Patricia (Journal of experimental botany, 2016)
Although plants are exposed to a great number of pathogens, they usually defend themselves by triggering mechanisms able to limit disease development. Alongside signalling events common to most such incompatible interactions, modifications of plasma membrane (PM) physical properties could be new players in the cell transduction cascade. Different pairs of elicitors (cryptogein, oligogalacturonides, and flagellin) and plant cells (tobacco and Arabidopsis) were used to address the issue of possible modifications of plant PM biophysical properties induced by elicitors and their links to other events of the defence signalling cascade. We observed an increase of PM order whatever the elicitor/plant cell pair used, provided that a signalling cascade was induced. Such membrane modification is dependent on the NADPH oxidase-mediated reactive oxygen species production. Moreover, cryptogein, which is the sole elicitor able to trap sterols, is also the only one able to trigger an increase in PM fluidity. The use of cryptogein variants with altered sterol-binding properties confirms the strong correlation between sterol removal from the PM and PM fluidity enhancement. These results propose PM dynamics as a player in early signalling processes triggered by elicitors of plant defence.
Keywords: buněčná membrána; fluidita membrány; Microscopy, Fluorescence; signální transdukce; Signal Transduction; Nicotiana; reaktivní formy kyslíku; Spectrometry, Fluorescence; Microscopy, Confocal; Disease Resistance; plant defence; Plant Diseases; fluorescenční spektrometrie; fluorescenční mikroskopie; konfokální mikroskopie; fluidity; membrane order; Reactive Oxygen Species; plasma membrane; Arabidopsis; Membrane Fluidity; tabák; nemoci rostlin; Cryptogein mutants; reactive oxygen species; elicitors; Cell Membrane; signalling.; odolnost vůči nemocem